Clinical Significance of Hyperbilirubinemia Among HIV-1–Infected Patients Treated with Atazanavir/Ritonavir Through 96 Weeks in the CASTLE Study - McDonald, Cheryl (Mary Ann Liebert, Inc., 2012)
CASTLE was a randomized 96-week study that demonstrated that atazanavir/ritonavir (ATV/r) was noninferior to lopinavir/ritonavir (LPV/r) in treatment-naïve HIV-infected patients. Analyses were carried out among patients who received ATV/r in the CASTLE study to better understand the clinical significance of unconjugated hyperbilirubinemia associated with administration of boosted ATV. Hyperbilirubinemia was defined as total bilirubin (conjugated and unconjugated) elevation greater than 2.5 times the upper limit of normal (grade 3–4). Patients in the ATV/r arm were assessed based on the presence or absence of hyperbilirubinemia through week 96. Analyses included number of confirmed virologic responders (CVR; HIV RNA <50 copies per milliliter), impact of hyperbilirubinemia on symptoms, elevations in liver enzymes, patient quality of life, and medication adherence. Through 96 weeks in the CASTLE study, 44% of patients who received ATV/r had hyperbilirubinemia at any time point, and between 12.5% and 21.6% had hyperbilirubinemia at any single study visit. At 96 weeks, 74% of patients overall and 84% and 69% of patients with and without hyperbilirubinemia, respectively, achieved CVR. Symptoms of jaundice or scleral icterus occurred in 5% of patients overall and in 11% with hyperbilirubinemia and 0% without hyperbilirubinemia. Four percent of patients with and 3% of patients without hyperbilirubinemia had grade 3–4 elevations in liver transaminases. Less than 1% of patients discontinued treatment due to hyperbilirubinemia. There were no differences in quality of life or adherence between patients with or without hyperbilirubinemia. In the CASTLE study, hyperbilirubinemia observed in the ATV/r group did not negatively impact clinical outcomes in HIV-infected patients.